Development of EXBOOK – M2J on Human Excretory System Materials to Improve Students' Collaboration Skills: Penelitian - Novinda Vira Fardiana; Firda Awalia Putri; Safwatun Nida (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to develop and test the validity and practicality of EXBOOK-M2J (Excretory Booklet - Mindful, Meaningful & Joyful Learning) learning media designed to improve students' collaboration skills on human excretory system material. This study used the ADDIE model R&D method with quantitative and qualitative approaches, with a one-group pretest-posttest research design. The validity test was carried out by a material and media expert, while readability was tested on VIII-grade students of SMP Negeri 2 Malang. The validation results show that this product is very valid and feasible. Implementation was carried out through a project-based learning model, which resulted in an increase in students' collaboration skills based on the comparison of the initial and final questionnaires. These results show that EXBOOK-M2J is effective as a project-based learning medium to develop 21st-century skills, especially collaboration.